Determining the cumulative energy demand and greenhouse gas emission of Swedish wheat flour - Wu, Yihan (2021)
Food production brought a tremendous impact on human society. However, there has been a lot of debate between organic and conventional farming. Producing enough food by maximizing the yield to feed the growing population has been the main goal of agriculture nowadays. This goal is achieved by applying different kinds of synthetic chemicals to improve the performance of crops in conventional farming. However, this leads to different environmental problems like soil degradation, loss of biodiversity, and disruption of healthy ecosystems. As a result, there is a growing demand for information on the environmental impact of food products from consumers and food supply chain participants. The main objective of the current study is to investigate the environmental impacts of organic and conventional wheat flour produced and supplied in Sweden, using life cycle analysis (LCA) and focusing on the global warming potential (GWP) and cumulative energy demand (CED). A cradle-to-gate LCA with the functional unit (FU) of 1 ton of wheat flour at the gate of the milling facility is conducted in this study. The results of the present study show that in terms of GWP, conventional systems have a higher emission compared to organic systems. As to energy demand, the two systems have almost similar results. The GWP for the conventional systems is 356 CO2-eq kg/FU while it is 249 CO2-eq kg/FU for the organic systems. The CED for the conventional system is 4025 MJ/FU while it is 3983 MJ/FU for the organic system. The farm activity is the hot spot stage for both conventional and organic systems. Overall, when considering environmental aspects, wheat flour from organic farming in Sweden is more sustainable than wheat flour from conventional farming systems. Increasing the yield for organic farming could improve further the environmental sustainability of organic wheat flour.